Autophagy induction regulates aquaporin 3‐mediated skin fibroblast ageing. (28th November 2021) - Xie, H.; Zhou, L.; Liu, F.; Long, J.; Yan, S.; Xie, Y.; Hu, X.; Li, J.
Summary: Background: Long‐ and short‐term ultraviolet (UV) exposure have distinct biological effects on human fibroblasts. Objectives: To elucidate the underlying mechanisms of the biological effects of UV exposure on human skin fibroblasts. Methods: We subjected human skin fibroblast cells with or without aquaporin 3 (AQP3), death effector domain‐containing protein (DEDD) or Beclin1 manipulation to UVA treatment and evaluated autophagy and senescence in them. Results: Short‐term UVA irradiation induced autophagy and upregulated AQP3 but not senescence, whereas long‐term UVA irradiation inhibited autophagy, AQP3 and trigger senescence in vitro and in vivo . Silencing AQP3 abolished short‐term UVA irradiation‐induced autophagy and led to cellular senescence, whereas AQP3 overexpression partially rescued the senescence and autophagy inhibition induced by long‐term UVA exposure in vitro . Mechanistically, the transcription factor Jun was found to bind to the AQP3 promoter to activate its transcription following short‐term UVA exposure. Subsequently, AQP3 interacted with DEDD to induce its ubiquitination‐mediated degradation and promote autophagy, and bound to Beclin1 to directly activate autophagy. Finally, autophagy induced by AQP3 overexpression robustly prevented UVA‐induced senescence in vitro and in vivo . Conclusions: Our study indicates that AQP3 controls skin fibroblast photoageing by regulating autophagy and represents a potential target for future interventions against skin ageing. Abstract : What is already known about this topic? Ultraviolet (UV) exposure is one of the leading causes of skin ageing and disease. Autophagy is an essential catabolic pathway that clears damaged cytoplasmic components and abnormal particles. Autophagy is linked to various diseases including skin ageing, but its relationship with UV in premature skin ageing remains controversial. Aquaporin 3 (AQP3) is the predominant aquaporin expressed in the skin and was recently found to be associated with autophagy in cancer cells. What does this study add? We observed a different response of autophagy and senescence in human dermal fibroblasts to short‐ or long‐term UVA exposure. Short‐term UVA irradiation induced autophagy and upregulated AQP3 but not senescence, whereas long‐term UVA irradiation inhibited autophagy, AQP3 and trigger senescence in vitro and in vivo . Autophagy induced by AQP3 overexpression robustly prevented UVA‐induced senescence in vitro and in vivo . What is the translational message? UV‐triggered cutaneous ageing severely compromises youthful appearance. Besides its function as a channel, AQP3 controls skin photoageing by regulating autophagy through direct interactions with DEDD/Beclin1. The sophisticated regulating mechanism of AQP3 may be one explanation for the diverse responses of skin cells to different doses of UV stimulation. AQP3 represents a potential target for future interventions against skin ageing. Linked Comment:  D. Bergamaschi. Br J Dermatol 2022; 186:211–212 . Plain language summary available online